Familial Relationships are More Beneficial than Those with Peers: Intrinsic Motivation Plays a Significant Role - M. Fadli Nugraha; Sairah Sairah (Psympathic : Jurnal Ilmiah Psikologi, 2024)
This research aimed to test two hypotheses with confidence, namely the effect of family support on positive affect through academic motivation, and the effect of friend support on positive affect through academic motivation. A qualitative method was used including the 268 participants collected through convenience sampling. The result of the research showed that family support has a significant influence on positive affect, while friend support had no significant impact. Furthermore, the role of academic motivation is consistent with the hypothesis, showing a strong correlation. This research also provides insightful discussions on limitations and offers valuable suggestions for further investigation.